Pelatihan Pengendalian Internal dan Sistem Informasi Perusahaan Bagi Karyawan PT Sarwa Inspirasi Konstruksi - Thomas Averio; Ricky Ricky (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this training activity is to provide broader understanding, knowledge, and insight to employees and management of the company regarding proper internal control and information systems within the company in order to minimize risk and maximize the company’s performance. This training activity is carried out using the lecture method. Participants of this training activity came from the employees and management of PT Sarwa Inspirasi Konstruksi, Pontianak, West Borneo. The number of participants for this training is 10 (person) participants. This training activity went very well because of the good cooperation and coordination of the various parties involved. This training activity is expected to have a positive contribution and impact on the development of the company in the future, both in terms of understanding of employees and company management regarding internal control and good information systems within the company so that the company can develop towards a better direction, more efficient and effective in carrying out the company's operational activities as well as minimizing the risks that may arise and can cause losses in the company.